Analytical Ultracentrifugation VIII
DOI: 10.1007/2882_005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Dodecameric Subunit of Lumbricus Hemoglobin

Abstract: For modeling the lowresolution shape of the dodecameric subunit of Lumbricus terrestris hemoglobin, experimental smallangle X-ray scattering (SAXS) data and ab initio modeling approaches using a genetic algorithm or simulated annealing have been applied. In addition to the use of strict ab initio approaches, procedures which additionally include available structural information concerning symmetry and shape in the form of constraints or templates have been employed to improve the results. Templates for the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 66 publications
0
2
2
Order By: Relevance
“…In contrast to previous findings (Zipper et al, 2006), owing to an improved set of experimental data, the comparison of the observed and predicted scattering behaviour of the dodecameric subunit of L. terrestris Hb does not hint at any obvious discrepancies between the shapes in solution and the crystal. The previously supposed discrepancies could be traced back to a hitherto overlooked deficiency in the desmeared experimental scattering curve, which led to underestimated particle dimensions in the previous studies (Krebs, Kuchumov et al, 1996;Zipper et al, 2006) as compared with the revised data in Table 1. As may be taken from the SAXS profiles ( Fig.…”
Section: Figurecontrasting
confidence: 93%
See 3 more Smart Citations
“…In contrast to previous findings (Zipper et al, 2006), owing to an improved set of experimental data, the comparison of the observed and predicted scattering behaviour of the dodecameric subunit of L. terrestris Hb does not hint at any obvious discrepancies between the shapes in solution and the crystal. The previously supposed discrepancies could be traced back to a hitherto overlooked deficiency in the desmeared experimental scattering curve, which led to underestimated particle dimensions in the previous studies (Krebs, Kuchumov et al, 1996;Zipper et al, 2006) as compared with the revised data in Table 1. As may be taken from the SAXS profiles ( Fig.…”
Section: Figurecontrasting
confidence: 93%
“…Some deficiencies in the previous desmearing procedure also necessitated a scrupulous re-evaluation of the initial SAXS data. The data in this paper are slightly different from the previous data (Krebs, Kuchumov et al, 1996), and recently supposed discrepancies between solution and crystal data (Zipper et al, 2006) have now been removed.…”
Section: Haemoglobin (Hb) From Lumbricus Terrestris (Earthworm)contrasting
confidence: 65%
See 2 more Smart Citations